Taking a New Look at Lexical Networks - Gaëtanelle Gilquin (Lexis: Journal in English Lexicology)
This article aims to investigate the empirical validity of the types of lexical networks found in the cognitive literature which account for the various senses of a polysemous word by showing how each sense is an extension of another. It starts from an existing network analysis, namely Norvig & Lakoff’s [1987] analysis of the verb take, and compares its structure with data obtained from corpora and a sentence production experiment. The assessment of the validity of Norvig & Lakoff’s model is both linguistic (does the model reflect frequency as attested in naturally-occurring language?) and cognitive (does the model reflect salience in the ordinary language user’s mind?). It is argued that the model does not stand up to the empirical validation proposed here, but that it may still have a role to play in a theory of polysemy.